"I Think When I Speak, I Don't Sound Like That": The Influence of Social Positioning on Rhetorical Skill Development in Science. (January 2019) - Falconer, Heather M.
Negotiating membership within a disciplinary community is as much an exercise in rhetorical facility as it is content expertise. Where individuals reside in the hierarchy of membership is determined by not only what they talk and write about, but how. Yet, there are many factors that can impact newcomers' acculturation into a disciplinary community on a rhetorical level. In this article, I use positioning theory and intersectional identity to examine how Anne, a woman of color participating in undergraduate research in science, learned to read and write as a scientist and the ways her social position as a woman, person of color, and low-income and first-generation student influenced her perception and adoption of the discourse as her own. I argue that social positioning influences students' views of scientific discourse and affects their rhetorical skill development as scientific writers. Because recognition as a group insider is heavily influenced by discourse, this research has potential implications for those interested in retention and persistence of women of color in STEM, as well as for those interested in changing learning cultures and incorporating writing instruction into disciplinary arenas.